2010
DOI: 10.1002/jor.21079
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pro‐inflammatory and immunoregulatory cytokines on human tenocytes

Abstract: Tendon injury induces a local inflammatory response, characterized by the induction of pro-inflammatory cytokines. The aim of the present study was to analyze the effects of TNFa, IL-6 and IL-10 on key parameters of tendon homeostasis. Cultured primary human tenocytes were treated with the recombinant cytokines IL-6, IL-10, TNFa, or combinations of TNFa with IL-6 and IL-10 (10 ng/mL, 6, 24 h). Expression of type I collagen, elastin, MMP-1, TNFa, IL-1b, IL-6, IL-10, and suppressors of cytokine signaling (SOCS1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
111
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(117 citation statements)
references
References 30 publications
6
111
0
Order By: Relevance
“…Remarkably, our data showed that PRP had potential to downregulate COL1A1, VEGF, COX-2, IL-6, and IL-6R. Other studies have shown that tumor necrosis factor-a-activated tenocytes express high levels of MMP-1, IL-1ß, and IL-6 [17]. Actually, the cell-extrinsic response to stressors can involve both functional gene categories; first gene products likely involved in inflammation and tissue level adaptations such as angiogenesis and second genes that regulate the extracellular matrix compartment, ie, fibrillar collagens and remodeling enzymes (ie, MMP-1, MMP-3, ADAMTS4, and ADAMTS5) [18].…”
Section: Discussionsupporting
confidence: 69%
“…Remarkably, our data showed that PRP had potential to downregulate COL1A1, VEGF, COX-2, IL-6, and IL-6R. Other studies have shown that tumor necrosis factor-a-activated tenocytes express high levels of MMP-1, IL-1ß, and IL-6 [17]. Actually, the cell-extrinsic response to stressors can involve both functional gene categories; first gene products likely involved in inflammation and tissue level adaptations such as angiogenesis and second genes that regulate the extracellular matrix compartment, ie, fibrillar collagens and remodeling enzymes (ie, MMP-1, MMP-3, ADAMTS4, and ADAMTS5) [18].…”
Section: Discussionsupporting
confidence: 69%
“…Proinflammatory cytokines, including TNF-a, IL-1b, IL-6, and IL-8, released upon injuries reduce the collagen production and induce vasodilation, angiogenesis, and matrix metalloproteinase (MMPs) expression in tendon repair (22)(23)(24). Chronic tendon injuries also involve inflammatory responses (22)(23)(24) closely associated with elevated MMP activities (25,26). The persistent inflammation and the disrupted balance between MMPs and tissue inhibitor of metalloproteinases (TIMPs) contribute to scarlike tendon healing and chronic matrix degradation (25,26).…”
mentioning
confidence: 99%
“…A blockage of TNF-a (28) and an inhibition of MMPs (29) improved tendon healing in vivo. To better understand how inflammation and MMP activities are regulated in tendon, a series of in vitro studies investigated molecular responses in tenocytes when stimulated by proinflammatory cytokines or M1 macrophages (Mfs) (23,30). TNF-a treatment up-regulated expression of MMP-1, proinflammatory (e.g., TNF-a and IL-1b), and anti-inflammatory (e.g., IL-6 and IL-10) cytokines in human tenocytes (23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cultured avian tendon cells exposed to TNF-␣ , an increased temperature, and mechanical stress led to a reduction of procollagen mRNA expression [Pan and Halper, 2003]. Cultured human tenocytes treated with TNF-␣ reduced their type 1 collagen deposition and highly upregulated their expression of pro-and immunoregulatory cytokines [John et al, 2010], and culturing tendon explants in the presence of TNF-␣ led to upregulation of the expression of Toll-like receptor 2 mRNA [de Mos et al, 2009].…”
Section: Introductionmentioning
confidence: 99%